Use of metaverse as innovation into educational technology to drive curriculum progress - Melyani Rizkia Putri; Arridho Alnajmuzzakki Farhan; Sarah Muslimah Hanif (Hipkin Journal of Educational Research, 2024)
Metaverse introduces significant innovation in education by enabling engaging three-dimensional learning experiences. Educational institutions are actively preparing for metaverse integration in the curriculum, enriching students' creativity and critical thinking. This research aims to investigate and identify how the use of the metaverse can be integrated as an innovation in educational technology. This research uses a qualitative approach by collecting data through literature study and data analysis techniques using content analysis methods to highlight the potential of the metaverse as an innovative tool in developing educational technology curricula. Metaverse as a technology that is not only popular in the field of technology but also in the field of education has brought new changes. In the world of education, metaverse allows teachers and students to interact with each other in a virtual room where there is no direct interaction. Overall, the influence of the Metaverse on curriculum design can create significant opportunities to improve the quality of learning. However, the implementation of metaverse in the education sector faces many obstacles and challenges that must be overcome in order to achieve optimal results, one of the main obstacles is limited technological infrastructure.   Abstrak Metaverse memperkenalkan inovasi signifikan dalam pendidikan dengan memungkinkan pengalaman belajar tiga dimensi yang menarik. Institusi pendidikan aktif mempersiapkan integrasi metaverse dalam kurikulum, memperkaya kreativitas dan pemikiran kritis siswa. Penelitian ini bertujuan untuk menyelidiki dan mengidentifikasi bagaimana penggunaan metaverse dapat diintegrasikan sebagai inovasi dalam teknologi pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data melalui studi pustaka dan teknik analisis data menggunakan metode analisis isi untuk menyoroti potensi metaverse sebagai alat inovatif dalam pengembangan kurikulum teknologi pendidikan. Metaverse sebagai teknologi yang tidak hanya populer di bidang teknologi namun juga bidang pendidikan telah membawa perubahan baru. Dalam dunia pendidikan, metaverse memungkinkan guru dan siswa berinteraksi satu sama lain dalam sebuah ruangan virtual di mana tidak ada interaksi langsung. Secara keseluruhan, pengaruh Metaverse pada desain kurikulum dapat menciptakan peluang yang signifikan untuk meningkatkan kualitas pembelajaran. Namun, implementasi metaverse dalam bidang pendidikan menghadapi banyak hambatan dan tantangan yang harus diatasi supaya dapat mencapai hasil yang optimal, salah satu hambatan utama adalah keterbatasan infrastruktur teknologi. Kata Kunci: Inovasi Pendidikan; Kurikulum; Metaverse